Object-Oriented Programming and Data Analysis using Java - Rosziati Ibrahim; Noor Azah Samsudin; Norhalina Senan; Muhammad Aamir (2021)
Object-oriented programming and data analysis using Java describes primary elements of object-oriented approach in problem solving using Java programming language. The use of class diagrams and benefits of object-oriented approach in the introductory chapter is very good to give preliminary knowledge to readers on object-oriented programming elements. Then, examples of Java code are used to explain the concept of the primary elements in object-oriented programming including object, class, constructor, inheritance, and polymorphism. Essentially, the inheritance topic is discussed in detail to promote code sharing and code reusability. The use of the primary elements in object oriented approach are also demonstrated in advanced applications of data structure, file processing, and data analysis. The target audience of this book include diploma and bachelor degree students in Computer Science and Information Technology.This book can also be used by artificial intelligence and data mining researchers who would like to experience Java implementation in data analysis experiments.